2021
DOI: 10.37481/sjr.v4i3.331
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengaruh Citra Merek Produk, Kualitas Produk, Dan Harga Diskon Terhadap Keputusan Pembelian Produk Minuman Kopi Pada Pengguna Aplikasi Grab Food Di Kota Medan

Abstract: This research was conducted in Medan City, West Medan District to observe the effect of Brand Image, Product Quality, Price Discounts on Coffee Drink Purchase Decisions for Grab Food application users in Medan City. This research process uses quantitive research. The population in this study itself is the entire community in West Medan District as many as 73,536 people. The sampling technique used in this study was Simple Random Sampling, with a total sample of 100 respondents. Data collection techniques using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
1
4
0
2
Order By: Relevance
“…Azzahra & Paludi (2023) revealed that purchasing decisions are influenced by product quality. Other research by Melati et al (2021) and Octhaviani & Sibarani (2021) shows that quality does not affect brand image or purchasing decisions.…”
Section: A Introductionmentioning
confidence: 89%
“…Azzahra & Paludi (2023) revealed that purchasing decisions are influenced by product quality. Other research by Melati et al (2021) and Octhaviani & Sibarani (2021) shows that quality does not affect brand image or purchasing decisions.…”
Section: A Introductionmentioning
confidence: 89%
“…Brand image is not just about the logo or physical appearance of the brand itself, but also includes the overall experience and perception formed by consumers about the brand. Brand image can be influenced by various factors, such as advertising, direct experience with the product, recommendations from friends or family, and people's general views of the brand (Octhaviani & Sibarani, 2021).…”
Section: Theoretical Basismentioning
confidence: 99%
“…Berdasarkan penelitian terdahulu variabel yang dimaksud adalah sebagai berikut: 1. Kualitas produk diteliti oleh (Anggraeni & Soliha, 2020), (Syamsidar & Soliha, 2019), (Rosanti et al, 2021), (Vikar et al, 2021), (Yuliana & Maskur, 2022), (Putra & Talumantak, 2022), (Nopendra et al, 2022), (Hakim diteliti oleh (Octhaviani & Sibarani, 2021). 9.…”
unclassified
“…& Juwita, 2021),(Laisina & Fairliantina, 2022),(Octhaviani & Sibarani, 2021),(Wati & Gunaningrat, 2022),(Salsabila & Maskur, 2022). 2.…”
mentioning
confidence: 99%
See 1 more Smart Citation